Asymmetries in global building envelope air infiltration and tightness data: Exploring knowledge gaps for accurate energy analyses - Rana Raafat; Sherif Goubran; Nahla N. Makhlouf; Mohsen Aboulnaga (Indoor Environments)
Air infiltration is one of the leading causes of energy loss and heat gain in indoor building spaces. It significantly burdens energy use for heating and cooling, affects indoor comfort and air quality, and increases CO2 emissions, intensifying climate change. While extensive field test results have been reported in the literature, this paper aims to investigate the comprehensiveness of this published data. The research synthesizes published field test data from more than 60 sources to provide benchmark infiltration values for different building typologies, construction methods, and climate zones. Additionally, climate data estimates the average energy burden of infiltration across various climate zones. The analysis highlights critical gaps in envelope infiltration data collection for non-residential buildings and significant gaps in geographic regions outside Europe, the U.S.A., and Canada. This paper presents three main guiding questions addressing key research gaps related to air infiltration in buildings and its impact on energy performance and indoor comfort. The proposed questions and answers aim to build upon existing knowledge, provide valuable insights for ongoing and future research, and inspire exploration into innovative strategies for improving building energy efficiency and occupant well-being. It also provides a list of actionable recommendations for air infiltration testing and research to address the now-apparent gaps.